Antimicrobial activity of the antibacterial peptide PMAP-36 and its analogues. (November 2019) - Zhou, Jiangfei; Liu, Yongqing; Shen, Tengfei; Chen, Liangliang; Zhang, Cong; Cai, Kairui; Liao, Chengshui; Wang, Chen
Abstract: The growing problem of antibiotic resistance has attracted people's attention; thus, the search for new antibacterial agents is imminent. In this study, a series of antimicrobial peptides (AMPs) based on the porcine antibacterial peptide PMAP-36 were designed by amino acid substitution to develop peptide analogues as new classes of antimicrobial agents. By extending the α-helix and increasing the positive charge, two peptide analogues, PMAP-36PW and PMAP-36PK, were synthesized. The antibacterial activities of PMAP-36 and its peptide analogues were detected in vitro and in vivo . The results showed that PMAP-36PW and PMAP-36PK had a broadened antibacterial spectrum compared to that of PMAP-36. After the modification, PMAP-36PW and PMAP-36PK exhibited antibacterial activities on swine Escherichia coli K88, while PMAP-36 did not. PMAP-36, PMAP-36PW and PMAP-36PK did not have antibacterial activities against Enterococcus faecium B21. PMAP-36 PW had significant antibacterial activity against seven bacterial strains compared to PMAP-36, and PMAP-36PK had significant antibacterial activity against five bacterial strains compared to PMAP-36. Furthermore, PMAP-36PW exhibited enhanced pH stability. Moreover, in the in vivo efficacy assessment of mice infected with Salmonella choleraesuis C78-1 and Listeria monocytogenes CICC 21533, the peptide analogues exhibited an impressive therapeutic effect by reducing bacterial gene copies and decreasing inflammatory damage in mouse livers and lungs, resulting in a reduction in mouse mortality. This study provides reference data for the design of clinically effective antibacterial peptides. Highlights: By extending the α-helix and increasing the positive charge, PMAP-36PW and PMAP-36PK, were synthesized. PMAP-36PW and PMAP-36PK had a broadened antibacterial spectrum compared to that of PMAP-36. PMAP-36PW and PMAP-36PK exhibited therapeutic effects in infected mice.